ANALYSIS OF STRATEGIC MANAGEMENT for ECOTOURISM DEVELOPMENT TOWARD COMMUNITY INVOLVEMENT AND NATURAL CONSERVATION at TM GUNUNG HALIMUN SALAK - Kurniawan Gilang Widagdyo (Faculty of Economic and Business, 2012)
This study was conducted in order to analyze ecotourism development within Taman Nasional Gunung Halimun Salak (TNGHS) area and determine association among its elements which is ecotourism activities, community involvement, and natural conservation. To convey comprehensive and factual result, theoretical considerations appear as basis for this study as well as qualitative and quantitative analysis. Some theories tend to be guidance that will be confront with qualitative data that was obtain from interview with several expertise and community’s representative and compare with questionnaire distribution to determine how significant association occur between those three variables. The statistical analysis explains that ecotourism deliver positive impact toward local community and natural conservationDOI: 10.15408/etk.v11i1.1871